Pengelompokan Kabupaten/Kota Berdasarkan Indeks Pembangunan Manusia Provinsi Jawa Timur Tahun 2023 - Muhammad Akmal Hafiz Abidin; Satria Raditya Nugroho; Sri Pingit Wulandari (Jurnal Cakrawala Akademika, 2024)
Quality human resources are the key to success in achieving goals, both individual and regional. One of the main indicators of the quality of human resources is the Human Development Index (HDI), which includes poverty, life expectancy, unemployment, education, and labor participation. East Java Province, with its diversity and large population, faces great challenges in improving the quality of human resources. One method of measuring whether these factors affect HDI is by dividing clusters based on the region, then analyzed using cluster analysis. Cluster analysis, both hierarchical and non-hierarchical methods, can be used to group cities/districts in East Java based on HDI indicators. This grouping is expected to assist the government in designing more targeted policies. In this practicum, a cluster analysis of HDI in 2023 was conducted using these methods. Data on factors affecting the Human Development Index (HDI) showed high variability, especially in the labor force participation rate, by fulfilling the assumptions of multivariate normal distribution and independence. Hierarchical cluster analysis showed two optimal clusters with the K-Means method: the first cluster included 13 districts/cities, while the second cluster contained 25 districts/cities. In the non-hierarchical cluster analysis, three clusters were formed with each member: 16 districts/cities in cluster 1, 10 in cluster 2, and 12 in cluster 3, and there were significant differences between clusters in the grouping of certain variables.